Port Community Systems: Accelerating the Transition of Seaports toward the Physical Internet—The Portuguese Case - Vítor Caldeirinha; João Lemos Nabais; Cláudio Pinto (Journal of Marine Science and Engineering, 2022)
Supply chains are complex systems that have grown in dimension and spread worldwide. In supply chains, physical and information flows have strict service quality requirements, namely transparency conditions and traceability. Seaports, connecting land and maritime transport, are special components of supply chains where multiple players interact with different perspectives, and conflicting goals may arise. Port community authorities invest in electronic platforms to foster communication and integration with the companies that interact with the seaport, guiding the digitization of the seaport business. In main European and world ports, the Port Community System (PCS) is the platform that supports the creation of a network composed of shipping agents, shippers, freight forwarders, transporters, terminals, logistics platforms, and public entities. PCS focuses on service level, partner networks, maritime services, freight services, logistical services, and advanced port services. These features have an impact on seaport operations, which affects supply chain performance. Digitization within the scope of the PCSs has fostered the development of horizontal collaboration between seaport community partners. The Physical Internet (PI) is an innovative concept that seeks new logistics solutions requiring integration and interoperability between partners in the supply chain, including maritime and land transport. This paper focuses on (i) the evolution guidelines of PCSs and (ii) on the PCS Business Factors that can drive the supply chain into a significant improvement in performance. A survey was sent to a sample of Portuguese supply chain experts regarding the causal relationship between PCS Business Factors and supply chain performance in the next 10 to 20 years. From the data collected, recent services evolving at PCS are promoting a mindset change aligned to the implementation of a Physical Internet. Establishing a Physical Internal in Portuguese seaports could take decades, but it will support the transition to a new phase of PCS, accelerating the transition from Isolated Supply Chains (I-SCs) to Open Supply Chains (O-SCs), thus improving supply chain performance.